Spatial spectral imaging as an adjunct to the Bethesda classification of thyroid fine‐needle aspiration specimens. Issue 3 (25th July 2012) - Hahn, Lewis D.; Hoyt, Clifford; Rimm, David L.; Theoharis, Constantine
Abstract BACKGROUND: Thyroid fine‐needle aspiration (FNA) biopsy, the preoperative diagnostic standard of care for patients with thyroid nodules, has limitations. Spectral imaging captures visible light information that is beyond the capability of the human eye, potentially increasing the accuracy of FNA biopsy. In the current study, the authors demonstrated the feasibility of using spectral imaging in combination with automated spatial analysis based on trainable pattern recognition as an adjunct test for thyroid FNA classification by developing an algorithm that distinguishes between images of papillary thyroid carcinoma (PTC) and benign goiter (BG). METHODS: A multispectral camera was used to capture spectral images representing 100 cases of PTC and BG. Used in conjunction with commercial software, 10 cases were used as a training set to develop a "classifier, " a classification algorithm that segments digitized multispectral images into regions of PTC, BG, and "nonfeature." This algorithm was used to generate a screening test and a diagnostic test that were validated on an independent set of images representing 30 cases of PTC and 30 cases of BG. RESULTS: The area under the receiver operating characteristic for the PTC/BG classifier was 0.90. The screening test had a sensitivity of 0.93 and a specificity of 0.73. The diagnostic test had a sensitivity of 0.70 and a specificity of 0.90. CONCLUSIONS: The authors developed image classification tests that distinguish between FNAs of PTC and BG, demonstrating the potential value of spatial spectral imaging as an adjunct test for the classification of thyroid FNA samples. The data support prospective testing to determine the value of the PTC/BG classifier in routine clinical use. Cancer (Cancer Cytopathol) 2013. © 2012 American Cancer Society.